Low-Temperature Annealing Induced Amorphization in Nanocrystalline NiW Alloy Films - Z. Q. Chen (Journal of Nanomaterials, 2013)
Annealing induced amorphization in sputtered glass-forming thin films was generally observed in the supercooled liquid region. Based on X-ray diffraction and transmission electron microscope (TEM) analysis, however, here, we demonstrate that nearly full amorphization could occur in nanocrystalline (NC) sputtered NiW alloy films annealed at relatively low temperature. Whilst the supersaturation of W content caused by the formation of Ni4W phase played a crucial role in the amorphization process of NiW alloy films annealed at 473 K for 30 min, nearly full amorphization occurred upon further annealing of the film for 60 min. The redistribution of free volume from amorphous regions into crystalline regions was proposed as the possible mechanism underlying the nearly full amorphization observed in NiW alloys.